Nilai-Nilai Kearifan Lokal Pada Wacana Ritual Adat “Helas Keta” Etnik Atoni Pah Meto: Kajian Etnolinguistik - Feka, Viktorius P.; Agnes M.D. Rafael (Unika Santu Paulus Ruteng, 2023)
This study aims to reveal the values of local wisdom of the Atoni Pah Meto Ethnic in the discourse of the traditional ritual “Helas Keta’ in Timor Island, East Nusa Tenggara, based on an ethnolinguistic perspective. This research employs qualitative-descriptive method. This research is conducted in the three stages namely data collection, data analysis, and data analysis display. The results of the study show that the traditional ritual